2012
DOI: 10.1186/1472-6882-12-139
|View full text |Cite
|
Sign up to set email alerts
|

Harpalycin 2 inhibits the enzymatic and platelet aggregation activities of PrTX-III, a D49 phospholipase A2 from Bothrops pirajai venom

Abstract: BackgroundHarpalycin 2 (HP-2) is an isoflavone isolated from the leaves of Harpalyce brasiliana Benth., a snakeroot found in northeast region of Brazil and used in folk medicine to treat snakebite. Its leaves are said to be anti-inflammatory. Secretory phospholipases A2 are important toxins found in snake venom and are structurally related to those found in inflammatory conditions in mammals, as in arthritis and atherosclerosis, and for this reason can be valuable tools for searching new anti-phospholipase A2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…As flavonoids can inhibit sPLA2 and consequently decrease its proinflammatory activity [ 26 , 28 , 29 ], the effect of 5CQA on sPLA2 was evaluated. Following subplantar injections of Swiss mice, sPLA2 had substantial potential to induce oedema after 60 min ( Figure 7(a) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As flavonoids can inhibit sPLA2 and consequently decrease its proinflammatory activity [ 26 , 28 , 29 ], the effect of 5CQA on sPLA2 was evaluated. Following subplantar injections of Swiss mice, sPLA2 had substantial potential to induce oedema after 60 min ( Figure 7(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…A paw oedema assay was performed using a previously described protocol [ 8 ]. Male Swiss mice (21 g) were anaesthetised by inhaling halothane.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, several articles have reported that natural antioxidant compounds, such as flavonoids and related substances, when given prior to sPLA2 injection, have significant anti-inflammatory activities. This probably stems from the ability of many of these compounds to partially inhibit the enzymatic and pharmacological activities of sPLA2 from Crotalus durissus terrificus, as well as from their strong antioxidant activities [53][54][55][56]97]. Thus, the search for new natural compounds with anti-inflammatory properties remains an important area of research.…”
Section: Resultsmentioning
confidence: 99%
“…Snake venom sPLA2 shares similar mechanisms of action and the same pathways of action with mammalian sPLA2. Experimental evidence in the literature demonstrates that both sPLA2 isoforms are able to induce inflammation and other similar biological activities [10,[17][18][19]. It is noteworthy that literature data demonstrate sPLA2 can activate signaling events that cannot be explained simply by its catalytic activity, and this fact emphasizes that sPLA2 could act essentially as a ligand of a receptor, rather than as an enzyme [20].…”
Section: Secretory Phospholipase A2mentioning
confidence: 99%
“…Edunol from Brongniartia podalyrioides (Leguminosae) reversed the toxic effects of B. atrox envenomation in rodent models [45]. Harpalycin 2 (HP-2) isolated from Harpalyce brasiliana (Papilionoideae) inhibited the enzymatic acitivity of piratoxin-III isolated from the venom of Bothrops pirajai [108].…”
Section: Natural Products In the Development Of Antivenom Agentsmentioning
confidence: 99%